2017
DOI: 10.1016/j.jascer.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of cobalt doping on the electrical conductivity of ZnO nanoparticles

Abstract: Cobalt doped zinc oxide (Zn 1-x Co x O; x = 0, 0.05, 0.10, 0.15) samples were synthesized using coprecipitation method. The Co doped ZnO nanoparticles showed the maximum solubility limit. The XRD patterns confirm the hexagonal type wurtzite structure without secondary phase in Co substituted ZnO samples. The particle size was studied using transmission electron microscope (TEM) and grain size estimated using scanning electron microscope (SEM). We report the study of temperature dependence of conductivity on Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Conductivity of nanoparticles depends upon grain size, morphology, and microstructure and it is ca. 1.5 × 10 −7 S/cm [ 59 ]. Because of the low volume fraction of ZnO NPs in CS-ZnO films (from 0 to 0.15 wt.%; see below the volume fraction calculation), the effective conductivity of nanocomposites practically depends upon the conductivity of neat CS ( ca .…”
Section: Discussionmentioning
confidence: 99%
“…Conductivity of nanoparticles depends upon grain size, morphology, and microstructure and it is ca. 1.5 × 10 −7 S/cm [ 59 ]. Because of the low volume fraction of ZnO NPs in CS-ZnO films (from 0 to 0.15 wt.%; see below the volume fraction calculation), the effective conductivity of nanocomposites practically depends upon the conductivity of neat CS ( ca .…”
Section: Discussionmentioning
confidence: 99%
“…The grain size reduced with increase of cobalt doping concentration whereas it forms densely packed network. It is clearly observed that for increase in cobalt concentration from 1% to 7% the grain size was found to be decreased [33,34] according to the figures 3(d), (e). Here it was noticed that the dopant deteriorate the degree of crystallization through its substitution.…”
Section: Surface Morphologymentioning
confidence: 76%
“…It should be noticed that the pristine ZnO with a wurtzite structure is a natural n-type semiconductor, provided by the deviations from stoichiometry and presence of intrinsic defects like oxygen vacancies and zinc interstitials [6]. The nonlinear log σ vs. T −1 behaviour was also observed for other donor-doped ZnO-based materials [31,32], and attributed to the temperature dependence of the contributions provided by the thermal excitation of electrons from donor levels to the conduction band, hopping between the impurity bands, oxygen vacancies, zinc interstitials and oxygen sorption–desorption processes to the overall charge transport mechanism. The activation energies for both high and low-temperature ranges (Table 1) significantly decrease for the doped materials as compared to the pristine ZnO, likely due to the electron donor effect.…”
Section: Resultsmentioning
confidence: 99%